Alignment in the Hospital-Physician Relationship: A Qualitative Multiple Case Study of Medical Specialist Enterprises in the Netherlands - Sander Ubels; Erik M. van Raaij (Kerman University of Medical Sciences, 2023)
Background  Policy-makers and hospital boards throughout the world have implemented different measures to create and sustain effective hospital-physician relationships. The 'integrated funding' policy reform in the Netherlands was aimed at increasing hospital-physician alignment and led to the unforeseen formation of medical specialist enterprises (MSEs): a fiscal entity representing all self-employed physicians in a hospital. It is unknown how hospitals and MSEs perceive their alignment and how they govern the relationship. This study explores the hospital-MSE relationship, and how governance styles influence perceived alignment in this relationship.Methods  A multiple case study of five non-academic hospitals in the Netherlands was performed. Data was derived from two sources: (1) analysis of hospital-MSE contracts and (2) semi-structured interviews with hospital and MSE board members. Contracts were analysed using a predefined contract analysis template. Interview recordings were transcribed and subsequently coded using the sensitizing concepts approach.Results  Contracts, relational characteristics, governance styles and perceived alignment differed substantially between cases. Two out of five contracts were prevention contracts, one was a mixed type, and two were promotion contracts. However, in all cases the contract played no role in the relationship. The use of incentives varied widely between the hospitals; most incentives were financial penalties. The governance style varied between contractual for two hospitals, mixed for one hospital and predominantly relational for two hospitals. Development of a shared business strategy was identified as an important driver of relational governance, which was perceived to boost alignment.Conclusion  Large variation was observed regarding relational characteristics, governance and perceived alignment. MSE formation was perceived to have contributed to hospital-physician alignment by uniting physicians, boosting physicians' managerial responsibilities, increasing financial alignment and developing shared business strategies. Relational governance was found to promote intensive collaboration between hospital and MSE, and thus may improve alignment in the hospital-physician relationship.